Tunable electrochemical behavior of dicarboxylic acids anchored Co-MOF: sensitive determination of rutin in pharmaceutical samples - Sivam, Thushatharcchini; Gowthaman, N. S. K.; Lim, H. N.; Andou, Yoshito; P., Arul; E., Narayanamoorthi; S., Abraham John (Elsevier, 2021)
Rutin (RT) also known as vitamin P, is an electroactive flavanoid mainly found in plants. It is generally applied as a clinical drug, Chinese traditional medicine and consumed as a supplement and act as a healthy collagen. Consumption of RT as supplement associated with some side effects and certain people has allergy towards RT. Therefore, it is meaningful to develop a fast, simple and reliable method to detect RT to avoid health risks. This paper describes the facile synthesis of Co-MOF using 1,4-benzenedicarboxylic acid (BDC) and biphenyl-4,4-dicarboxylic acid (BPDC) as ligands through solvothermal method. The XRD patterns and FT-IR spectra confirm the formation of Co-BDC and Co-BPDC MOFs. Moreover, the SEM images revealed that the Co-BDC MOF possesses a stacked layer of MOF while Co-BPDC MOF shows a flower-like MOF. The Co-BDC and Co-BPDC MOFs were fabricated on GC electrode for the sensitive determination of RT. The ligands with different chain lengths in the MOFs have influenced the interaction of RT with the MOF. The Co-BPDC-MOF/GCE exhibited an excellent electrocatalytic activity than the Co-BDC-MOF/GCE and the fabricated electrode was successfully utilized for the determination of RT in pharmaceutical samples. The fabricated sensor exhibited the limit of detection of 0.03 µM (S/N = 3) and the superior sensitivity of 781.43 µA/mM/cm2 in the linear range detection of 0.5 – 1000 µM RT with excellent repeatability, reproducibility, and good anti-interference ability.